Implementation of a care bundle improves PBC management - Rachel Smith; Laura Burke; Nadir Abbas; Richard J. Aspinall; Douglas Thorburn; Michael Heneghan; Andrew Yeoman; Joanna Leithead; Conor Braniff; Robert Mitchell-Thain; Rebecca L. Jones; Stuart McPherson; et al. (JHEP Reports)
Background & Aims: In 2021, we conducted a UK-wide audit of the management of primary biliary cholangitis (PBC) in the National Health Service (NHS) of the UK, which identified widespread deficiencies in PBC-related healthcare. In the current study, recognising the need to address these deficiencies, we aimed to (1) develop a PBC care bundle to support clinicians in the provision of high-quality, standardised care; (2) pilot the bundle in selected centres across the UK; and (3) re-evaluate adherence to quality standards. Methods: We designed a PBC care bundle that incorporated a checklist of quality standards and a summary of guidelines from the British Society of Gastroenterology. Twelve hospitals, with variable performance in the national audit, were invited to pilot the bundle between 1 October 2023 and 31 March 2024. Clinical data were collected to compare adherence to quality standards before and after bundle use. Results: We obtained data about 773 patients with PBC. We found significant improvement in performance across all quality standards following bundle use, with two hospitals achieving target performance (≥90%) across all standards, something not achieved by any hospital in the national audit. Across all centres, referral of patients for second-line therapy increased from 72% to 94% (p <0.001). Assessment of symptoms improved from 54% to 90% (p <0.001), and bone health improved from 65% to 86% (p <0.001). Surveillance for hepatocellular carcinoma increased from 67% to 97% (p <0.001), and screening for gastro-oesophageal varices improved from 81% to 92% (p = 0.027). Conclusions: Use of the PBC care bundle significantly improves adherence to management guidelines. Rollout of the bundle will mark a vital step to improve the delivery of high-quality care to all patients with PBC. Impact and implications: The national primary biliary cholangitis (PBC) audit demonstrated critical shortfalls in the delivery of PBC-related healthcare across the UK. In this study, we have designed a PBC care bundle to improve adherence to management guidelines and promote standardised care. We show that use of the bundle improves care delivery in hospitals across the NHS. The PBC care bundle has been endorsed by the British Society of Gastroenterology and the British Association for the Study of the Liver and is freely available online to all clinicians to support the provision of high-quality PBC-related healthcare.